REAKSI PASAR MODAL TERHADAP PENGUMUMAN TARIF TRUMP UNTUK INDONESIA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM INDEKS LQ45 - Richard Imanuel Sangkoy; Maryam Mangantar; Joy Elly Tulung (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study aims to analyze the capital market reaction to events before and after the announcement of the 32% US tariff on Indonesia on manufacturing companies listed on the LQ45 index. Market reaction is measured through Abnormal Return and Trading Volume Activity with a quantitative approach using the Event Study method. The sample was determined using purposive sampling, with a sample size of six manufacturing companies listed on the LQ45 index for the period May-July 2025. The testing was conducted using a paired sample t-test and Wilcoxon signed rank test with an observation period of 7 days before and 7 days after the announcement. The results showed that there was no significant difference in abnormal return or trading volume activity before and after the tariff announcement. Thus, the announcement of a 32% tariff by the United States on Indonesia did not cause a significant reaction in the Indonesian capital market